DEVELOPMENT OF SCIENTIFIC APPROACH BASED STUDENT WORKSHEET ON ANIMAL TOPICS FOR 10th GRADE - Adriana YD Lumban Gaol; Natalia Sihombing; Erlintan Sinaga (Jurnal Pelita Pendidikan, 2022)
This study aims to design and produce Student Worksheets (LKPD) based on the Scientific Approach for animalia material for 10th-grade students in SMA Yayasan Perguruan Utama Medan. The research used a research and development methodology. The design of the Scientific Approach-based LKPD was carried out using the 4-D development model, namely Define, Design, Development, and Disseminate. The research results show that the developed LKPD based on the scientific approach received a "very feasible" assessment from learning experts at 97.7%, from subject matter experts at 85.71%, and from design experts at 97.9%. Additionally, subject teachers also assessed it as "very feasible" at 96.87%, and students provided a "positive" assessment with a score of 95.96%. The effectiveness test of the developed LKPD based on the scientific approach showed an N-Gain value of 0.64 with a "moderate" criterion. The results of this study indicate that the LKPD for animalia material can be used in the learning process.